Self-responsibility predicts the successful outcome of coronary artery bypass surgery - C. J. Eales; T. D. Noakes; A. V. Stewart; P. Becker (AOSIS, 2004)
Purpose: This study was designed to determine whether the acceptance of self-responsibility is an important determinant of the successful outcome of coronary artery bypass graft (CABG) surgery. The success of this costly intervention may be limited unless patients understand and adhere to the prescribed medical regimen, including diet and exercise after surgery. Patients suffering from chronic diseases must take charge of their own health and not abrogate that responsibility to the care providers. Method: Questionnaires were designed to determine aspects of improved quality of life and self-responsibility. For the study, 73 patients who had undergone CABG surgery were selected from surgical patients in the private as well as the public sector. In order to assess the acceptance of self-responsibility, the spouses/care-givers of the patients were included in the study. Patients were interviewed during the first few days after the operation when they had returned to the wards and again six months and 12 months later. Successful outcome was measured in terms of improved quality of life using the criteria suggested by the Coronary Artery Surgery Study (Coronary Artery Surgical Study Principal Investigators, 1983). The acceptance of self-responsibility was then investigated as a possible factor influencing the improvement of the quality of life of these patients. Results: The acceptance of self-responsibility was a significant factor predicting the successful outcome of CABG surgery in the group of patients who achieved an improved quality of life following surgery (p<0.01). From the results of this study, a profile of South African patients with improved quality of life was identified. They are: Men, married, annual income > R50 000 (US $8 000), who had a normal sex-life prior to the operation.  They differ significantly from the group without an improved quality of life in the following aspects: they spend more hours participating in sport at school (p=0.04), stop their sporting activities for a shorter period of time  prior to the operation (p<0.01) and are taller (p<0.01). Twelve months after the operation their sexual performance has improved (p<0.01) and they are not depressed (p<0.01). Patients who accept self-responsibility for their recovery after CABG surgery have the following characteristics:  married (p<0.01), have a level of education > grade 12 (p=0.01), have  an annual income > R50 000 (p=0.05). They differ from the group who did not accept personal responsibility in that they and their spouses/care-givers had a greater knowledge about the disease and the risk factor modification (p=0.01; p<0.01), and twelve months after the operation the patients are satisfied with the outcome of the operation (p<0.01). Conclusions: A stepwise logistic regression established that the acceptance of self-responsibility was the strongest  factor predicting an improved quality of life after CABG surgery. Patients who did not accept responsibility did not have an improved quality of life irrespective of the impact of all other parameters. Patients' satisfaction with the outcome of the operative procedure is an important predictor of the acceptance of self-responsibility. Realistic expectations of the outcome of CABG surgery will improve patients' satisfaction with the outcome. The knowledge of the spouse is a significant factor in the patients' acceptance of self-responsibility. Knowledge of the chronic nature of their disease as well as risk factor modification and realistic expectations of the outcome of CABG surgery influences patientsacceptance of self-responsibility.